The Effect of Garlic Powder Concentration and Salt (NaCl) on the Quality of Tofu During Storage at Room Temperature - Prita Lestari Ningrum; Rona J Nainggolan; Ridwansyah Ridwansyah (Jurnal Rekayasa Pangan dan Pertanian, 2014)
The research was conducted to determine the effect of garlic powder concentration and salt (NaCl) on the quality of tofu during storage at room temperature. The research had been performed using a completely randomized design with two factors, i.e. garlic powder concentration (B) : (0%), (3%), (6%), and (9%) and salt concentration (N) : (0%), (2,5%), (5%), dan (7,5%). Parameters analyzed were total microbes, pH of tofu, pH of submerged solution, moisture content, ash content, protein content, salt content, and sensory characteristics (color, aromatic, flavor, and texture). The results showed that garlic powder concentration had highly significant effect on total microbes, pH of tofu, pH of submerged solution, ash content, protein content, and sensory characteristics (color, aromatic, flavor, and texture). Salt concentration had highly significant effect on pH of tofu, pH of submerged solution, moisture content, ash content, protein content, salt content, and sensory characteristics (color, aromatic, and flavor). Interaction of both factors had highly significant effect on pH of tofu, pH of submerged solution, ash content, protein content, and sensory characteristics (aromatic and flavor). Garlic powder concentration of 6% and salt concentration of 5% was the best treatment for the quality of tofu. Keywords : Garlic powder concentration, salt concentration, tofu.